Ganancia Rápida de Peso en Atletas de Lucha Durante el Campeonato Panamericano, Lima 2018 [Rapid Weight Gain in Wrestling Athletes During the Panamerican Championship, Lima, 2018 - Herrera-Valenzuela, T (ARAN Ediciones S.A., 2020)
Introduction: to avoid rapid body mass fluctuations and the associated effects on health and performance, some combat sports federations have made changes to regulations. Objective: the objective of this study was to analyze the impact of the Rapid Weight Gain on sporting success in elite Olympic wrestling athletes under the new weigh-in procedure. Methods: the body mass of 75 athletes was recorded during the Pan-American Olympic wrestling Championship (Lima, 2018), corresponding to 29 % of the total universe of competitors (n = 255). Of these, 29 were Greco-Roman style, eight freestyle, and 38 women´s wrestling. The official weigh-in was carried out between 8:00 and 8:30 hours. As for the second weigh-in, this was done with the same official weigh-in scale, immediately before the first match (between 10:00 and 11:00 hours). Rapid Weight Gain after weigh-in was compared between medalist and non-medalist athletes. Results: when analyzing the difference between medalists and non-medalists, no significant differences were found in Greco-Roman athletes (t = 0.114; p = 0.910; r = 0.022), in freestyle (Mann-Whitney U = 5,500; p = 0.486; r = 0.000), in women´s wrestling (Mann-Whitney U = 163.0; p = 0.774; r = 0.124), and in all competitors (Mann-Whitney U = 641.5; p = 0.855; r = 0.037). Conclusions: no significant differences were found between medalist and non-medalist athletes in any of the Olympic wrestling styles. © 2020 SENPE y and Arán Ediciones S.L. Este es un artículo.